MOTHER'S ANXIETY WITH MEASLES IMMUNIZATION FOR 12 MONTHS CHILDREN DURING THE COVID-19 PANDEMIC IN GUMAYUN VILLAGE DUKUHWARU DISTRICT - Ratna Widhiastuti; wisnu widyantoro; Novia Tri Ayu Wulandari (Indonesian Journal for Health Sciences, 2023)
Immunization does not go smoothly during this pandemic due to anxiety and fear of taking the baby or toddler out of the house vaccination. This study aims to determine the relationship between maternal stress and the immunization of measles children aged 12 months during the Covid-19 pandemic 30 respondent in Gumayun Village, Dukuhwaru Subdistrict. The data collection tools used in this study were questionnaires and checklist sheets. The results of data analysis using a chi-square statistical test showed ρ value of 0.002 0.05 and a confidence interval of 95%, which means  Ho was rejected and Ha was accepted. So it is concluded that there is a link between maternal anxiety and measles immunization of children aged 12 months during the Covid-19 pandemic in Gumayun Village, Dukuhwaru Subdistrict.